2000
DOI: 10.1029/1999jd900937
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of solar UV by clouds: A comparison between satellite‐derived cloud effects and ground‐based radiation measurements

Abstract: Abstract. Assessment of the effects of ozone depletion on biologically effective solar UV at ground level has been greatly advanced through the use of remote sensing data. Satellite data on atmospheric properties allow the construction of geographically distributed surface UV radiation maps based on radiative transfer calculations. In this respect, clouds play a dominant but rather complex role. We compared the reduction of daily UV doses due to clouds, as derived from satellite cloud data, with the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 27 publications
2
39
0
3
Order By: Relevance
“…However, in some recent studies the groundbased/satellite measurements and model simulations have been used to identify changes in the surface UV and processes responsible for the UV radiation changes (e.g. McElroy, 1993, Borderwijk et al, 1995;Zerefos et al, 1995;Krzyścin, 1996;Weatherhead et al, 1997;Udelhofen et al, 1999;den Outer et al, 2000;Kaurola et al, 2000;Matthijsen et al, 2000;Eerme et al, 2002). These studies confirm that the UV changes are driven by various factors: ozone, cloudiness, aerosols, and surface albedo.…”
Section: Introductionmentioning
confidence: 84%
“…However, in some recent studies the groundbased/satellite measurements and model simulations have been used to identify changes in the surface UV and processes responsible for the UV radiation changes (e.g. McElroy, 1993, Borderwijk et al, 1995;Zerefos et al, 1995;Krzyścin, 1996;Weatherhead et al, 1997;Udelhofen et al, 1999;den Outer et al, 2000;Kaurola et al, 2000;Matthijsen et al, 2000;Eerme et al, 2002). These studies confirm that the UV changes are driven by various factors: ozone, cloudiness, aerosols, and surface albedo.…”
Section: Introductionmentioning
confidence: 84%
“…Stratospheric ozone is especially important because it is the major atmospheric absorber of solar UV-B radiation (e.g. UNEP, 1998;Matthijsen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud effects for summer periods derived from the International Satellite Cloud Climatology Project (IS-CCP) data -cloud fraction and optical depth -perform a little worse than derived from the reflectivity (Matthijsen et al, 2000;Williams et al, 2004). Daily sums of UV irradiance using ISCCP data indicate a similarly good performance with respect to the standard deviations .…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have demonstrated the ability (and limitations) of spaceborne measurements to assess the groundlevel UV radiation (Eck et al, 1995;Herman et al, 1999;Kalliskota et al, 2000;Matthijsen et al, 2000;Krotkov et al, 2001;Kazantzidis et al, 2006;Arola et al, 2009;Kazadzis et al, 2009). Cloud effects for summer periods derived from the International Satellite Cloud Climatology Project (IS-CCP) data -cloud fraction and optical depth -perform a little worse than derived from the reflectivity (Matthijsen et al, 2000;Williams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation